Pengembangan Permen Jelly "Previmin” Multivitamin Mineral untuk Pencegahan Stunting: Pengembangan Permen Jelly ”Previmin” Multivitamin Mineral untuk Pencegahan Stunting - Ryveka, Aurellia; Lestari, Lily Arsanti; Pratiwi, Dessy; Sundjaya, Tonny (Amerta Nutrition, 2023)
Background: The prevalence of stunting in Yogyakarta province has decreased in 2022, although it hasn't reached the target of 14%. The Taburia supplementation program, implemented by the Indonesian government in 2010, aimed to address this issue, but its effectiveness remains a concern. Therefore, in 2017 jelly candy with fortification of Taburia and prebiotics fructooligosaccharides was developed as well as an organoleptic test in preschool and kindergarten children. Subsequently, in 2022, the production of the same jelly candy, named "Previmin" was upscaled and carried out in a factory. Production on a factory scale can change the nutritional contents and organoleptic properties of the product. Objectives: To evaluate the organoleptic properties, acceptability, and nutritional content of factory-scale "Previmin” jelly candy. Methods: This was true experimental study carried out in Kalurahan Sumberarum, Kapanewon Moyudan, Sleman District, Yogyakarta to evaluate the organoleptic properties and acceptability of jelly candy "Previmin'' on 59 toddlers. The production process was conducted by PT Natural Food Success, whereas nutritional content analysis was carried out in BBSPJIA Laboratory Bogor. Results: Based on organoleptic tests, the color, flavor, taste, and texture score were above 5 points hence respondents liked "Previmin”. As many as 75% of respondents could consume the product hence Previmin's acceptability was good. Nutritional content, heavy metals, and microbial count have good results and comply with SNI standards. Conclusions: Most toddlers like and can consume "Previmin” jelly candy. "Previmin” jelly candy contains a good source of macronutrients and micronutrients as well as has complied with SNI standards.